ANALISIS PENENTUAN SPESIALISASI SEKTOR DI KABUPATEN BOYOLALI DALAM MENGHADAPI IMPLEMENTASI OTONOMI DAERAH: MASA KRISIS EKONOMI1997-1999 - Siti Fatimah Nurhayati; Haris Haris (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
The implementation of local autonomy which focusing on the empowering local potencies is predictably running well if only the local specialized potencies can be highly optimalized. Normally, a well-developed specialized sector will support another under-developed sector. In this research, the writer attempts to analyse factors causing structural changes of economy and what kind of sectors that is possible to be made as socialized sectors in Boyolali regency. The research period taken in this research is in the time of economy crisis attacking Indonesia in 1997 - 1999 by taking some variables, i.e. PDRB, job vacancy per sector and specialized factors. The research use Classic shift share analysis method, Estheban-Marquilas shift share analysis and also Location-quotient analysis. As we know, Esteban-Marquilas shift share analysis is a new modification of classical shift share analysis. This technical change the influence of competitive spatiality into the influence of good competitive Esteban-Marquilas also involve allocation influence comprising the third specialized component of shift share technical as well as to the forth component of shift share namely the influence of allocation.